Beyond the three monkeys of workforce diversity: Who hears, sees, and speaks up? - Kusku, Fatma; Araci, Ozlem; Tanriverdi, Veysi; Ozbilgin, Mustafa F. (Frontiers in Psychology, 2022)
The purpose of the study is to explain differences between employees who feel a sense of belonging and who feel a sense of otherness in terms of their opinions about diversity works in their organizations. We conducted an empirical study to examine the perceptual differences between two independent groups of the study “who feel a sense of belonging” and “who feel a sense of otherness”. We collected data from 792 employees working for organizations in different sizes, industries, and capital structures enriched the representativeness of the sample. The findings show that out-group members remain less satisfied with diversity works in their organizations based on four main issues as “competence of diversity actors”, “embeddedness of diversity works in organizational policies/practices”, “diversity awareness in the HRM functions”, and “diversity-related employee satisfaction”. This paper makes two contributions. First, it contributes to the extant literature an understanding of the differences between those who remain indifferent to diversity works and those who care to see, speak and hear about it. Second, with a few exceptions, extant studies on diversity works have been dominated by Western-centered research. Research is needed on countries with different macro-contextual conditions, such as different legal regulations, socio-political status, and history. For this study, survey data were collected from people who work in Turkey, a country which has limited legal measures, underdeveloped discourses for equality, diversity, and inclusion. The paper provides significant insights for leading diversity works in national settings with less developed supportive mechanisms for diversity.